The antiarrhythmic compound efsevin directly modulates voltage‐dependent anion channel 2 by binding to its inner wall and enhancing mitochondrial Ca2+ uptake. (25th March 2020) - Wilting, Fabiola; Kopp, Robin; Gurnev, Philip A.; Schedel, Anna; Dupper, Nathan J.; Kwon, Ohyun; Nicke, Annette; Gudermann, Thomas; Schredelseker, Johann
Abstract : Background and Purpose: The synthetic compound efsevin was recently identified to suppress arrhythmogenesis in models of cardiac arrhythmia, making it a promising candidate for antiarrhythmic therapy. Its activity was shown to be dependent on the voltage‐dependent anion channel 2 (VDAC2) in the outer mitochondrial membrane. Here, we investigated the molecular mechanism of the efsevin–VDAC2 interaction. Experimental Approach: To evaluate the functional interaction of efsevin and VDAC2, we measured currents through recombinant VDAC2 in planar lipid bilayers. Using molecular ligand‐protein docking and mutational analysis, we identified the efsevin binding site on VDAC2. Finally, physiological consequences of the efsevin‐induced modulation of VDAC2 were analysed in HL‐1 cardiomyocytes. Key Results: In lipid bilayers, efsevin reduced VDAC2 conductance and shifted the channel's open probability towards less anion‐selective closed states. Efsevin binds to a binding pocket formed by the inner channel wall and the pore‐lining N‐terminal α‐helix. Exchange of amino acids N207, K236 and N238 within this pocket for alanines abolished the channel's efsevin‐responsiveness. Upon heterologous expression in HL‐1 cardiomyocytes, both channels, wild‐type VDAC2 and the efsevin‐insensitive VDAC2 AAA restored mitochondrial Ca 2+ uptake, but only wild‐type VDAC2 was sensitive to efsevin. Conclusion and Implications: In summary, our data indicate a direct interaction of efsevin with VDAC2 inside the channel pore that leads to modified gating and results in enhanced SR‐mitochondria Ca 2+ transfer. This study sheds new light on the function of VDAC2 and provides a basis for structure‐aided chemical optimization of efsevin.